2017
DOI: 10.3892/ol.2017.7616
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation inhibitor MLN4924 induces G2 cell cycle arrest, DNA damage and sensitizes esophageal squamous cell carcinoma cells to cisplatin

Abstract: Abstract. Inhibiting the protein neddylation pathway using the NEDD8-activating enzyme inhibitor MLN4924 represents an attractive anticancer strategy having been demonstrated to exhibit promising anticancer efficacy and with tolerable levels of toxicity; however, the mechanism by which MLN4924 inhibits cell proliferation in human esophageal squamous cell carcinoma (ESCC) cells requires further investigation. The present study revealed that MLN4924 treatment led to G 2 cell cycle arrest and enhanced the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…As MLN4924 and cisplatin are both known to induce DNA damage and are used in clinical practice for the treatment of specific malignancies, the effects of combined MLN4924 and cisplatin treatment on pancreatic cancer cells were investigated in the present study. This hypothesis was verified in esophageal squamous cell carcinoma (24). The results demonstrated that MLN4924 + cisplatin treatment significantly suppressed pancreatic cancer growth both in vitro and in vivo, and that combined treatment was well tolerated by the mice.…”
Section: Discussionmentioning
confidence: 60%
“…As MLN4924 and cisplatin are both known to induce DNA damage and are used in clinical practice for the treatment of specific malignancies, the effects of combined MLN4924 and cisplatin treatment on pancreatic cancer cells were investigated in the present study. This hypothesis was verified in esophageal squamous cell carcinoma (24). The results demonstrated that MLN4924 + cisplatin treatment significantly suppressed pancreatic cancer growth both in vitro and in vivo, and that combined treatment was well tolerated by the mice.…”
Section: Discussionmentioning
confidence: 60%
“…Evasion of cell cycle arrest is most frequently observed in tumor development [ 34 , 35 ]. One of the anticancer mechanisms of chemotherapeutic agents is the induction of cell cycle arrest in cancer cells [ 36 , 37 ]. It has been reported that the combination of other agents with DDP significantly induces various levels of cell cycle arrest in OS cells [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CCK-8 and colony-forming experiments performed in the present study demonstrated that simvastatin significantly inhibited the proliferation of SACC-83 cells in a time- and concentration-dependent manner. Cancer cell proliferation is usually accompanied by cell cycle arrest, and cell cycle progression is modulated by cyclin-dependent kinase inhibitors ( 41 , 42 ). In the present study, an increased number of SACC-83 cells were arrested at the G 1 phase following simvastatin treatment; however, further investigation is required to elucidate the underlying mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%